Social work and child welfare politics : through Nordic lenses - Forsberg, Hannele; Kröger, Teppo (Policy Press, 2010)
Drawing on contemporary research and debates from different Nordic countries, this book examines how social work and child welfare politics are produced and challenged as both global and local ideas and practices.